Generating electricity from molecular bonding-correlated piezoresponse of biodegradable silk nanofibers. (1st December 2022) - Sohn, Changwan; Kim, Hyunseung; Han, Jihoon; Lee, Ki-Tae; Šutka, Andris; Jeong, Chang Kyu
Abstract: Many biomaterials have been proposed as eco-friendly piezoelectric materials. This research investigates the piezoelectricity of an electrospun silk nanofiber membrane for biodegradable piezoelectric energy harvesters. The molecular phase transition of silk fibroin inducted by ethanol from α-helix phase to β-sheet phase was observed. The reorganized phase structure of silk fibroin affects the dipole moment of molecular hydrogen bonds. Interestingly, we found that the piezoelectric response of silk fibroin nanofibers is declined by the conventional poling process which is usually considered as enhancing piezoelectric properties. This is due to the breaking of hydrogen bonds by an external high electric field, which causes deterioration of the silk fibroin dipole moment. This new phenomenon can be defined as 'inverse depolarization' and 'quasi-piezoelectricity' of protein-based biopolymers. The electrospun silk piezoelectric (ESP) generators are fabricated using high-quality piezoresponse of silk fibroin nanofiber membranes with confirming biodegradability. Finally, an EtOH-immersed ESP generator is attached to different body parts to be utilized as a self-powered motion-detecting sensor. In this work, we have thoroughly investigated the origin of piezoelectricity of an important biomaterial and also demonstrated high-performance energy harvesting devices with specific sensor applications, compared to previously reported other biomaterials. Graphical Abstract: ga1 Highlights: Phase-controlled Bombyx mori silk fibroin with piezoelectric properties is achieved into nanofibers membrane uniformly. Piezoelectric properties of silk fibroin deteriorate after electrical input process, called 'inverse depolarization'. Molecular hydrogen bonding is broken by an external high electric field, called 'quasi-piezoelectricity'. Semi-crystalline β phase of silk fibroin nanofibers is well optimized from amorphous α-helix phase for high piezoelectricity. Biodegradable self-powered flexible devices are fabricated using the highly-efficient piezoelectric silk nanofibers.